Need Analysis of LKPD Development based on Metacognitive Approach in Science Learning in Elementary School: Analisis Kebutuhan Pengembangan LKPD berbasis Pendekatan Metakognitif dalam Pembelajaran IPA di Sekolah Dasar - Rarastika, Nur; Arfah, Siti (Universitas Muhammadiyah Sidoarjo, 2022)
One of the success factors in learning science is meeting the learning needs of students. Science learning emphasizes the process of building a more complex understanding of science concepts in students. To optimize science learning, the learning process should be accompanied by learning resources such as teaching aids or student worksheets (LKPD) that can encourage students to expand their understanding. This study aims to analyze the needs of elementary school students about the development of LKPD based on a metacognitive approach. This type of research is descriptive qualitative. Data was collected through interviews, tests, questionnaires and document analysis. The subjects of this study were 42 fifth grade students and 2 classroom teachers. The results of this study indicate that elementary school students need learning resources in the form of student worksheets based on a metacognitive approach. This can be seen from the results of data analysis that as many as 52.37% get an average score to below the average which indicates students still have a low understanding of science concepts, there are no student worksheets that facilitate increasing the ability to understand science concepts, and student worksheets used are still conventional.